Effects of parent-child physical activity intervention on gross motor skills among preschoolers in China - Jia, Zhao; Abdullah, Borhannudin; Omar Dev, Roxana Dev; Samsudin, Shamsulariffin (Human Resource Management Academic Research Society, 2024)
The purpose of this quantitative study is to investigate the effect of parent-child physical activity intervention on children’s gross motor skills including child’s locomotor and child’s object control skills. A total of 64 children aged 5 to 6 and their parents from Changzhi city in China were divided into two group to participate in the experimental parent-child physical activity intervention program in this study. The Test of Gross Motor Development-2 was used in the pre-test and pro-test of experiments. The findings show that parent-child physical activity intervention program had a significant effect on children’s gross motor skills including children’s locomotor skills and the object control skills. The findings indicated that it is necessary for parents to provide opportunities for their children to engage in physical activity that promote a diversity of motor skills.